Pseudo-input signal generation for smart structural control and fast seismic response analysis - Akehashi, Hiroki; Wang, Bohan (Frontiers in Built Environment, 2025)
A pseudo-input signal generation method that realizes the pre-specified structural responses is proposed for fast and accurate analysis. The proposed generation method is based on the singular value decomposition and unit impulse responses in a discrete time system. When the given conditions cannot be fully satisfied, the proposed method provides approximate signals. One of the most effective uses of the proposed method is the replacement of the leading part of the original input ground motion by the generated input ground motion with the smaller time steps. This leads to an efficient and accurate analysis of the structural responses because the responses under the leading part of the original motion are accurately simulated by the generated motion. Furthermore, the proposed method is applicable not only to a single-point input ground motion but also to multiple-point input ground motions. The effectiveness of the proposed method is demonstrated through numerical examples. Moreover, it is explained that the proposed method can be applied to the characterization of pulse-like ground motions, the generation of finite impulse ground motions, and the down-sampling of input signals.